Dialektatlas Mittleres Westdeutschland (DMW) - Methodik, Akquise, Exploration und Analyse - Wallmeier, Nadine; Kuhmichel, Katrin; Gehrke, Gero; Sauermilch, Stephanie (Niederdeutsches Wort)

Messung der Fähigkeit zur Unterrichtsplanung bei Lehramtsstudierenden - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Ursachen für Veränderungen des physikdidaktischen Wissens im Studium - Joswig, Ann-Kathrin; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Basismodelle in Unterrichtsplanungen im Praxissemester Physik - Buschhütter, David; Mutschler, Tanja; Schröder, Jan; Riese, Josef; Borowski, Andreas (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Entwicklung eines Fachpraktikums im Techniklehramt - Ermel, Dorothee; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Wie entwickeln sich Wissen und Fähigkeiten im Physiklehramtsstudium? - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Wien 2019)

Estimation of acoustic wave non-linearity in ultrasonic measurement systems - Claes, Leander; Steidl, Carolin; Hetkämper, Tim; Henning, Bernd (arXiv.org)

Does Informational Equivalence Preserve Strategic Behavior? Experimental Results on Trockel’s Model of Selten’s Chain Store Story - Duman, Papatya (Games)
The purpose of this study is to experimentally test Trockel’s game, which is a modelling of the classical Chain Store Game (CSG), and determine whether one of the two theories of Equality and Deterrence may better account for the observed behavior. The CSG is an example of a simple game in extensive form where the actual behavior of well-informed players cannot be expected to agree with the clear results of game theoretical reasoning. To explain the disagreement between the theory and the expected behavior, Trockel’s game is proposed as an alternative modelling of the scenario. The existence of more than one equilibrium in Trockel’s game opens a door for reputation building. This study is the first attempt to experimentally test this alternative game with the same purpose. According to my data, there is some evidence in favor of both Equality and Deterrence Hypotheses. However, since the strategies compatible with the Equality Hypothesis are played more frequently, I observe some patterns which share the same intuition with the Deterrence Hypothesis.
Keywords: Applied Mathematics; Statistics; Probability and Uncertainty; Statistics and Probability

Gemeinsam Forschung gestalten. Handreichung zu partizipativer Forschung - Lutz, Katharina; Offergeld, Jana; Freymuth, Nina; Arp, Anna Liza

Frühe alltagsintegrierte mathematische Bildung. Eine Einleitung - Bruns, Julia; Vogtländer, A. (Frühe alltagsintegrierte mathematische Bildung. Handreichung für Lehrende)

Situative Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mathematik – Entwicklung und Validierung eines Testinstruments - Bruns, Julia; Strahl, Carolin; Gasteiger, Hedwig (Unterrichtswissenschaft)
Zusammenfassung Frühe mathematische Bildung findet in der Kindertagesstätte insbesondere in spontanen Alltagssituationen statt. Damit diese Alltagssituationen zu natürlichen Lernsituationen für die Kinder werden, müssen (angehende) frühpädagogische Fachkräfte zunächst das mathematische Potenzial in diesen Situationen erkennen. Diese Fähigkeit zur situativen Beobachtung und Wahrnehmung ist bisher unzureichend erforscht, was unter anderem auf begrenzte Methoden zur standardisierten Erfassung dieses Konstrukts zurückzuführen ist. Um diesem Bedarf zu begegnen, wurde das videobasierte Testinstrument Vimas_num zur Erfassung der Fähigkeit zur situativen Beobachtung und Wahrnehmung angehender frühpädagogischer Fachpersonen im Bereich Mengen und Zahlen entwickelt. Auf der Grundlage von drei aufeinander aufbauenden Studien wird die Validität verschiedener Aspekte der Testwertinterpretation untersucht. Die Ergebnisse geben Hinweise auf die Validität der Testwertinterpretation in Bezug auf den Testinhalt, die interne Struktur des Tests und die Zusammenhänge mit theoretisch verbundenen Konstrukten.
Keywords: Education

Interaktionen in mathematischen Spielsituationen in Kindertagesstätte und Familie - Meyer, Lena; Tabeling, Laura; Gasteiger, Hedwig; Bruns, Julia (Beiträge zum Mathematikunterricht 2020)

Adaptionshandlungen von Multiplikatorinnen und Multiplikatoren zur frühen mathematischen Bildung – Beschreibung und Bewertung aus fachbezogener Perspektive - Bruns, Julia; Schopferer, Theresa; Gasteiger, Hedwig (Journal für Mathematik-Didaktik)
Zusammenfassung Die Implementation früher mathematischer Bildung in Kindertagesstätten kann durch fachdidaktische Fortbildungen für frühpädagogische Fachkräfte unterstützt werden. Um Fachkräfte in der Breite zu erreichen, erscheint ein scaling up Ansatz geeignet, bei dem aufbauend auf das Fortbildungskonzept EmMa – Erzieherinnen und Erzieher machen Mathematik Multiplikatorinnen und Multiplikatoren qualifiziert werden. Dabei ergibt sich die Herausforderung, dass Fortbildende im Elementarbereich kaum mathematisches und mathematikdidaktisches Wissen mitbringen. Der Kontext dieser Studie ist der scaling up Prozess der Fortbildung EmMa unter diesen Umständen. Das Erkenntnisinteresse liegt in der Beschreibung und Bewertung der Adaptionshandlungen der Multiplikatorinnen und Multiplikatoren. Für die Bewertung der Adaptionen werden zwei Kriterien herangezogen: (1) das Kriterium der Präzision, das die Vollständigkeit und Klarheit der Inhalte umfasst und (2) das Kriterium der fachlichen Korrektheit, das durch das Ausbleiben fachbezogener Fehler beschrieben wird. Analysiert werden dabei die theoretischen, fachbezogenen Phasen der von Multiplikatorinnen und Multiplikatoren durchgeführten Fortbildung zur frühen mathematischen Bildung, da davon ausgegangen wird, dass insbesondere diese theoretischen Inhalte für diese Gruppe von Multiplikatorinnen und Multiplikatoren eine Herausforderung darstellen. Zur Untersuchung wurde eine videogestützte, qualitative Feldstudie mit N = 8 Fällen durchgeführt. Mit Hilfe der qualitativen Inhaltsanalyse wurden die Adaptionshandlungen der Multiplikatorinnen und Multiplikatoren charakterisiert und hinsichtlich ihrer Präzision und der fachlichen Fehler in diesen Adaptionen analysiert. Dabei zeigte sich, dass der eigenständige Umgang mit den mathematischen und mathematikdidaktischen Inhalten des Fortbildungskonzepts EmMa trotz intensiver Unterstützung anspruchsvoll und bei vielen Multiplikatorinnen und Multiplikatoren mit fachbezogenen Fehlern verbunden ist. Implikationen dieser Ergebnisse für die weitere Forschung werden diskutiert.

Situational Perception in Mathematics (SPiM)—Results of a Cross-Country Study in Austria and Norway - Bruns, Julia; Carlsen, Martin; Eichen, Lars; Erfjord, Ingvald; Hundeland, Per Sigurd (Mathematics Education in the Early Years)

Mathematisches Fachwissen von frühpädagogischen Fachpersonen im Spannungsfeld zwischen Disziplin- und Praxis - Bruns, Julia (Beiträge zum Mathematikunterricht 2020)

“Why don’t you make a drawing?" Motivation and strategy use in mathematical modelling - Schönherr, Johanna; Blomberg, J.; Schukajlow, S.; Rellensmann, J. (Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education: PME)

Measuring and investigating strategic knowledge about drawing to solve geometry modelling problems - Schönherr, Johanna; Schukajlow, S.; Leopold, C. (ZDM – Mathematics Education)

Paderborner Qualitätsstern zur Einschätzung der Kooperation im Übergang Kita – Grundschule. Herausgegeben von: Höke, Julia; Büker, Petra, Ogrodowski, Jana & Vollmann, Britta. Unter Mitarbeit von Alina Bruyn und Theresa Driller. Dieses Instrument liegt seit 2021 ebenfalls in vollständiger englischer Übersetzung vor: https://blogs.uni-paderborn.de/pq3-international/ - Herding, Jana

Zur Bedeutung von Integrationserfahrungen in der Grundschulzeit aus der Retroperspektive junger Erwachsener: eine Interviewstudie - Herding, Jana; Ogrodowski, J. (Diversität und soziale Ungleichheit. Herausforderungen an die Integrationsleistung der Grundschule. Jahrbuch Grundschulforschung)

Digitale Transformationsprozesse in der beruflichen Benachteiligtenförderung – erste Ergebnisse einer qualitativen Studie - Schemmer, Susanne Jutta (Digitalisierung am Übergang Schule Beruf. Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)

Lebenswelten und soziale Netzwerke von jungen Geflüchteten und Zugewanderten am Übergang in Ausbildung und Beruf - Schemmer, Susanne Jutta; Heisler, Dietmar (bwp@Berufs-und Wirtschaftspädagogik – online, (24.06.2020))

Semantic-based End-to-End Learning for Typhoon Intensity Prediction - Zahera, H.M.A (Arxiv)

ProBERT: Product Data Classification with Fine-tuning BERT Model. - Zahera, H.M.A; Sherif, Mohamed (MWPD@ ISWC)

On the multi-domain compact finite difference relaxation method for high dimensional chaos: The nine-dimensional Lorenz system - Kouagou, N.J.; Dlamini, P.G.; Simelane, S.M. (Alexandria Engineering Journal)
In this paper, we implement the multidomain compact finite difference method to numerically study high dimensional chaos by considering the nine-dimensional Lorenz system. Most of the existing numerical methods converge slowly for this kind of problems and this results in inaccurate approximations. Though highly accurate, the compact finite difference method becomes less accurate for problems characterized by chaotic solutions, even with an increase in the number of grid points. As a result, in this work, we adopt the multidomain approach. This approach remarkably improves the results as well as the efficiency of the method.
Keywords: Multidomain; Compact finite difference; 9D Lorenz system

Geschlechterverwirrungen. Was wir wissen, was wir glauben und was nicht stimmt
In Geschlechterfragen kann jede*r mitreden – und ist dabei oft von Irrtümern und Vorurteilen geleitet. 32 Autorinnen und Autoren befassen sich in diesem Band mit unserem Wissen, Glauben und Nichtwissen zu Geschlecht und »Gender«. Die Beiträge, die von historischen über philosophische und körperbezogene bis zu politischen Themen reichen, wollen sachkundig informieren, seriös aufklären – und auch ein wenig verwirren, indem sie ihren Gegenstand von unterschiedlichen Seiten betrachten und dabei zeigen, was wir nicht wissen.

Parameterized complexity of abduction in Schaefer’s framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (Journal of Logic and Computation)
Abstract Abductive reasoning is a non-monotonic formalism stemming from the work of Peirce. It describes the process of deriving the most plausible explanations of known facts. Considering the positive version, asking for sets of variables as explanations, we study, besides the problem of wether there exists a set of explanations, two explanation size limited variants of this reasoning problem (less than or equal to, and equal to a given size bound). In this paper, we present a thorough two-dimensional classification of these problems: the first dimension is regarding the parameterized complexity under a wealth of different parameterizations, and the second dimension spans through all possible Boolean fragments of these problems in Schaefer’s constraint satisfaction framework with co-clones (T. J. Schaefer. The complexity of satisfiability problems. In Proceedings of the 10th Annual ACM Symposium on Theory of Computing, May 1–3, 1978, San Diego, California, USA, R.J. Lipton, W.A. Burkhard, W.J. Savitch, E.P. Friedman, A.V. Aho eds, pp. 216–226. ACM, 1978). Thereby, we almost complete the parameterized complexity classification program initiated by Fellows et al. (The parameterized complexity of abduction. In Proceedings of the Twenty-Sixth AAAI Conference on Articial Intelligence, July 22–26, 2012, Toronto, Ontario, Canada, J. Homann, B. Selman eds. AAAI Press, 2012), partially building on the results by Nordh and Zanuttini (What makes propositional abduction tractable. Artificial Intelligence, 172, 1245–1284, 2008). In this process, we outline a fine-grained analysis of the inherent parameterized intractability of these problems and pinpoint their FPT parts. As the standard algebraic approach is not applicable to our problems, we develop an alternative method that makes the algebraic tools partially available again.
Keywords: Logic; Hardware and Architecture; Arts and Humanities (miscellaneous); Software; Theoretical Computer Science

Parameterised Complexity of Model Checking and Satisfiability in Propositional Dependence Logic - Mahmood, Yasir; Meier, Arne (Lecture Notes in Computer Science)

DeepWind: An Accurate Wind Turbine Condition Monitoring Framework via Deep Learning on Embedded Platforms - Ghasemzadeh Mohammadi, Hassan; Arshad, Rahil; Rautmare, Sneha; Manjunatha, Suraj; Kuschel, Maurice; Jentzsch, Felix Paul; Platzner, Marco; Boschmann, Alexander; Schollbach, Dirk (2020 25th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

Design and Implementation of a ReconOS-based TensorFlow Lite Delegate Architecture - Jentzsch, Felix P.
Modern machine learning (ML) techniques continue to move into the embedded system space because traditional centralized compute resources do not suit certain application domains, for example in mobile or real-time environments. Google’s TensorFlow Lite (TFLite) framework supports this shift from cloud to edge computing and makes ML inference accessible on resource-constrained devices. While it offers the possibility to partially delegate computation to hardware accelerators, there is no such “delegate” available to utilize the promising characteristics of reconfigurable hardware. This thesis incorporates modern platform FPGAs into TFLite by implementing a modular delegate framework, which allows accelerators within the programmable logic to take over the execution of neural network layers. To facilitate the necessary hardware/software codesign, the FPGA delegate is based on the operating system for reconfigurable computing (ReconOS), whose partial reconfiguration support enables the instantiation of model-tailored accelerator architectures. In the hardware back-end, a streaming-based prototype accelerator for the MobileNet model family showcases the working order of the platform, but falls short of the desired performance. Thus, it indicates the need for further exploration of alternative accelerator designs, which the delegate could automatically synthesize to meet a model’s demands.

Global generalized solutions to a forager–exploiter model with superlinear degradation and their eventual regularity properties - Black, Tobias (Mathematical Models and Methods in Applied Sciences)
Keywords: Applied Mathematics; Modeling and Simulation

Synergetic modulation of the electronic structure and hydrophilicity of nickel–iron hydroxide for efficient oxygen evolution by UV/ozone treatment - Pan, Ying; Wu, Yanfang; Hsain, H. Alex; Su, Ran; Cazorla, Claudio; Chu, Dewei (Journal of Materials Chemistry A)
Enhanced OER performance of Ni(Fe) hydroxide through UV/ozone treatment.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Assessment of electrocatalytic activity through the lens of three surface area normalization techniques - Ren, Hangjuan; Pan, Ying; Sorrell, Charles C.; Du, Haiwei (Journal of Materials Chemistry A)
Electrocatalytic activities of electrodes for water splitting are assessed via geometric area, BET surface area and ECSA normalisations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Enhanced electrocatalytic oxygen evolution by manipulation of electron transfer through cobalt-phosphorous bridging - Pan, Ying; Ren, Hangjuan; Chen, Ruizhe; Wu, Yanfang; Chu, Dewei (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Sprachsensible Formulierung von Erhebungsinstrumenten - Schwabl, Franziska; Janssen, Elmar A.; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

An Algorithmic Solution for Adaptable Real-Time Applications - Khaluf, Lial; Rammig, Franz-Josef (the International Journal On Advances in Software)

Zirkel und Lineal ohne Parallelenaxiom: Ein konstruktiver Zugang zur hyperbolischen Geometrie. - Hoffmann, Max (Der Mathematikunterricht)

Die Bedeutung unterschiedlicher Heterogenitätsmerkmale für das Erleben von Zustandsangst vor dem Sportunterricht in der Grundschule - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia; Korte, J. (Grundschulsport. Empirische Einblicke und pädagogische Empfehlungen)

Von Interkultureller Kompetenz und sportpädagogischem Können in postmigrantischen Gesellschaften. Grundlagen und Weiterentwicklung eines Forschungsprogramms - Grimminger-Seidensticker, Elke; Gieß-Stüber, P.; Möhwald, Aiko Julia (Sport im Kontext globaler Zusammenarbeit)

Sportdidaktik - Grimminger-Seidensticker, Elke; Oesterhelt, V.; Gerlach, E.; Friedrich, G. (Lernen im Fach und über das Fach hinaus)

Zum Umgang mit Heterogenität im Sportunterricht - Grimminger-Seidensticker, Elke; Frohn, J. (Empirie des Schulsports)

Machthandlungen von Schüler*innen im Sportunterricht – Welche Rolle spielt das Sportlehrer*innenhandeln? - Grimminger-Seidensticker, Elke (sportunterricht)

Körperbild, Bewegung und Sport in der Wahrnehmung von Grundschulkindern. Ergebnisse einer explorativen lnterviewstudie - Grimminger-Seidensticker, Elke; Korte, J.; Möhwald, Aiko Julia (sportunterricht)

A 14-weeks intervention study on changing preservice teachers’ psychological perspectives related to teaching inclusively: Explicit and implicit attitude, self-efficacy, and stress perception towards inclusion - Grimminger-Seidensticker, Elke; Lautenbach, F.; Heyder, A.; Korte, J.; Möhwald, Aiko Julia (Frontiers in Education)

Quantitative and qualitative results of a body image pilot intervention in (pre)adolescent girls - Grimminger-Seidensticker, Elke; Korte, J. (Journal of Physical Education & Health)

Health concepts among socially disadvantaged children in France, Germany and Switzerland - Grimminger-Seidensticker, Elke; Aceti, Monica; Knobé, Sandrine; Vieille Marchiset, Gilles (Health Promotion International)
Summary As health concepts develop through exposure to, and experience with particular contexts, and as health concepts influence health behaviour, it is important for actors in health promotion programmes to understand an individual’s health concepts. This study focussed on health concepts among socially disadvantaged children in France, Germany, Italy and Switzerland—a hitherto less researched population group. We conducted focus groups with a total of 167 children aged 7–11 years (mean=8.76 years, SD=0.68). The aim of this study was to explore if the life situation across four different countries leads to similar health concepts, and how the particular, national health discourses are reflected in the children’s health concepts. The data were analysed through a structured qualitative content analysis and revealed four categories: ‘Symbols/symptoms of health/illness’, ‘Emotionality’, ‘Healthy/unhealthy practices’, and ‘Consequences of health problems’. The children’s health concepts are linked to concrete events and objects, and they are able to think in logical sequences. However, the children’s causal argumentation is uni-dimensional; they do not cover the complexity of the development of health problems. In particular, overweight stands for illness and is exclusively the result of unhealthy practices. In their concepts, the children reflect the national health promotion programme discourses about overweight. They seem to understand the messages of health education as ‘behaving well means being healthy’; however, such a health education message initiates accusations of ‘unhealthy persons’. In consequence, challenges for sensitive health education programmes (at school) are discussed.

A 14-Week Intervention Study on Changing Preservice Teachers’ Psychological Perspectives on Inclusion: Explicit and Implicit Attitudes, Self-Efficacy, and Stress Perception Toward Inclusion - Lautenbach, Franziska; Korte, Johanna; Möhwald, Aiko; Heyder, Anke; Grimminger-Seidensticker, Elke (Frontiers in Education)

SUBCLINICAL DISORDERED EATING AND BODY DISSATISFACTION IN NORMAL WEIGHT CHILDREN—THE ROLE OF PHYSICAL ACTIVITY AND MOTIVES TO EXERCISE - Grimminger-Seidensticker, Elke; Korte, Johanna; Möhwald, Aiko; Trojan, Jörg (Journal of Physical Education & Health)

Der Koran in seinem religions- und weltgeschichtlichen Kontext. Eschatologie und Apokalyptik in den mittelmekkanischen Suren - Ghaffar, Zishan

Der Koran in seinem religions- und weltgeschichtlichen Kontext. Eschatologie und Apokalyptik in den mittelmekkanischen Suren - Ghaffar, Zishan
Review von Holger Zellentin, Review of Qur'anic Research, Vol. 7 no. 5 (2021) Rezension von Bertram Schmitz, Theologische Literaturzeitung, Nr. 7, 2021, Spalte 657-658 Review von Sebastian Bitsch, Der Islam, Band 98, Heft 2, 2021, 591-598

Spectral Asymptotics for Kinetic Brownian Motion on Surfaces of Constant Curvature - Kolb, Martin; Weich, Tobias; Wolf, Lasse Lennart (arXiv:2011.06434)
The kinetic Brownian motion on the sphere bundle of a Riemannian manifold $M$ is a stochastic process that models a random perturbation of the geodesic flow. If $M$ is a orientable compact constantly curved surface, we show that in the limit of infinitely large perturbation the $L^2$-spectrum of the infinitesimal generator of a time rescaled version of the process converges to the Laplace spectrum of the base manifold.

Körperspannung trainieren : auf die richtige Spannung kommt es an - Körperspannung als zentrale Lernvoraussetzung im (Gerät-)TurnenKörperspannung trainieren: auf die richtige Spannung kommt es an - Körperspannung als zentrale Lernvoraussetzung im (Gerät-)Turnen - Dörrer, Hans-Joachim; Köster, Carolin (Sportpädagogik)

Language Teachers and Crowdsourcing - Arhar Holdt, Špela; Zanasi, Lorenzo; Weber, Tassja; Volodina, Elena; Rodosthenous, Christos; Ordulj, Antonia; Miloshevska, Lina; Lazić Konjik, Ivana; Koeva, Svetla; Kasperavičienė, Ramunė; Hatipoglu, Ciler; Fort, Karën; et al. (Rasprave Instituta za hrvatski jezik i jezikoslovlje)
The paper presents a cross-European survey on teachers and crowdsourcing. The survey examines how familiar language teachers are with the concept of crowdsourcing and addresses their attitude towards including crowdsourcing into language teaching activities. The survey was administrated via an online questionnaire and collected volunteers’ data on: (a) teachers’ experience with organizing crowdsourcing activities for students/pupils, (b) the development of crowdsourced resources and materials as well as (c) teachers’ motivation for participating in or employing crowdsourcing activities. The questionnaire was disseminated in over 30 European countries. The final sample comprises 1129 language teachers aged 20 to 65, mostly working at institutions of tertiary education. The data indicates that many participants are not familiar with the concept of crowdsourcing resulting in a low rate of crowdsourcing activities in the classroom. However, a high percentage of responding teachers is potentially willing to crowdsource teaching materials for the language(s) they teach. They are particularly willing to collaborate with other teachers in the creation of interactive digital learning materials, and to select, edit, and share language examples for exercises or tests. Since the inclusion of crowdsourcing activities in language teaching is still in its initial stage, steps for further research are highlighted.
Keywords: Linguistics and Language; Language and Linguistics

Präpositionen und Deutsch als Fremdsprache: Quantitative Fallstudien im Lernerkorpus MERLIN - Weber, Tassja
Die Dissertation beschäftigt sich mit dem Gebrauch von Präpositionen (z. B. an, für) und Präpositionalphrasen (z. B. an der Wand, für dich) durch Lernende des Deutschen als Fremdsprache (DaF). Es wird untersucht, welche ausgewählten Variablen den Gebrauch dieser Strukturen beeinflussen. Der Schwerpunkt liegt dabei auf Gebrauchsschwierigkeiten. Auf Basis lernersprachlicher Daten im digitalen, frei verfügbaren Lernerkorpus MERLIN (merlin-platform.eu) und unter Berücksichtigung grundlegender Annahmen aktueller Spracherwerbstheorien werden quantitativ ausgerichtete Fallstudien zu folgenden Einflussvariablen durchgeführt: Die Erstsprache der Lernenden, die Sprachkompetenz, die syntaktische Funktion der PP und der semantische Gehalt der Präposition. Die Arbeit bettet sich ein in die Lernerkorpusforschung an der Schnittstelle zur Zweit- und Fremdspracherwerbsforschung. Die Ergebnisse zeigen insgesamt für alle Einflussvariablen einen Effekt und bestätigen damit den Einfluss intralingualer sowie interlingualer Merkmale im Sprachgebrauch von Lernenden. Dabei wird deutlich, dass die Gebrauchsschwierigkeiten nicht quantitativer (Korrektheit), sondern eher qualitativer Natur (Fehlertypen) sind. Die Dissertation liefert empirisch fundierte Erkenntnisse zu Schwierigkeiten im Gebrauch von Präpositionen und PP durch DaF-Lernende, für die bisher systematische, korpusgestützte Untersuchungen fehlten. Die Arbeit zeigt dabei exemplarisch auf, wie Annahmen aus der Spracherwerbsforschung anhand von Lernerkorpusdaten überprüft und mögliche Einflussvariablen im Sprachgebrauch ermittelt werden können. Die Erkenntnisse sind auch für andere Forschungsfelder (u.a. Fremdsprachenunterricht und maschinelle Sprachverarbeitung) relevant.
Keywords: Deutsch als Fremdsprache; Korpuslinguistik; Lernerkorpora; Präpositionen; Präpositionalphrasen; Grammatik; Regressionsanalyse

Noether’s-type theorems on time scales - Anerot, Baptiste; Cresson, Jacky; Hariz Belgacem, Khaled; Pierret, Frederic (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Noether’s-type theorems on time scales - Anerot, Baptiste; Cresson, Jacky; Hariz Belgacem, Khaled; Pierret, Frederic (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

CP2K: An electronic structure and molecular dynamics software package - Quickstep: Efficient and accurate electronic structure calculations - Kühne, Thomas; Iannuzzi, Marcella; Ben, Mauro Del; Rybkin, Vladimir V.; Seewald, Patrick; Stein, Frederick; Laino, Teodoro; Khaliullin, Rustam Z.; Schütt, Ole; Schiffmann, Florian; Golze, Dorothea; Wilhelm, Jan; et al. (The Journal of Chemical Physics)
CP2K is an open source electronic structure and molecular dynamics software package to perform atomistic simulations of solid-state, liquid, molecular, and biological systems. It is especially aimed at massively parallel and linear-scaling electronic structure methods and state-of-theart ab initio molecular dynamics simulations. Excellent performance for electronic structure calculations is achieved using novel algorithms implemented for modern high-performance computing systems. This review revisits the main capabilities of CP2K to perform efficient and accurate electronic structure simulations. The emphasis is put on density functional theory and multiple post–Hartree–Fock methods using the Gaussian and plane wave approach and its augmented all-electron extension.

A Submatrix-Based Method for Approximate Matrix Function Evaluation in the Quantum Chemistry Code CP2K - Lass, Michael; Schade, Robert; Kühne, Thomas; Plessl, Christian (Proc. International Conference for High Performance Computing, Networking, Storage and Analysis (SC))
Electronic structure calculations based on density-functional theory (DFT) represent a significant part of today's HPC workloads and pose high demands on high-performance computing resources. To perform these quantum-mechanical DFT calculations on complex large-scale systems, so-called linear scaling methods instead of conventional cubic scaling methods are required. In this work, we take up the idea of the submatrix method and apply it to the DFT computations in the software package CP2K. For that purpose, we transform the underlying numeric operations on distributed, large, sparse matrices into computations on local, much smaller and nearly dense matrices. This allows us to exploit the full floating-point performance of modern CPUs and to make use of dedicated accelerator hardware, where performance has been limited by memory bandwidth before. We demonstrate both functionality and performance of our implementation and show how it can be accelerated with GPUs and FPGAs.

Janus-type dual emission of a Cyclometalated Iron(III) complex - Bauer, Matthias; Steube, Jakob; Päpcke, Ayla; Bokareva, Olga; Reuter, Thomas; Demeshko, Serhiy; Schoch, Roland; Hohloch, Stephan; Meyer, Franc; Heinze, Katja; Kühn, Oliver; Lochbrunner, Stefan
Photoactive compounds are essential for photocatalytic and luminescent applications, such as photoredox catalysis or light emitting diodes. However, the substitution of noble metals, which are almost exclusively used, by base metals remains a major challenge on the way to a more sustainable world.1 Iron is a dream candidate for this ambitious aim.2 But compared to noble metal complexes that show long-lived metal-to-ligand charge-transfer (MLCT) states, realization of emissive and photoactive iron complexes is demanding, due to the fast deactivation of charge transfer states into non-emissive inactive states. No MLCT emission has been observed for monometallic iron complexes before. Consequently, dual emission could also not yet be realized with iron complexes, as it is a very rare property even of noble metal compounds. Here we report the Fe III complex [Fe(ImP) 2 ][PF 6 ] (HImP = 1,1’-(1,3-phenylene)bis(3-methyl-1-imidazol-2-ylidene)), showing Janus-type dual emission by combining LMCT (ligand-to-metal charge transfer) with MLCT luminescence. The respective excited states are characterized by a record lifetime of τ MLCT = 4.2 ns, and a moderate τ LMCT = 0.2 ns. Only two emissive Fe III compounds are known so far and they show LMCT luminescence only.3,4 The unique properties of the presented complex are caused by the specific ligand design combining four N-heterocyclic carbenes with two cyclometalating groups, using the σ-donor strength of six carbon atoms and the acceptor capabilities of the central phenyl rings. Spectroscopically, doublet manifolds could be identified in the deactivation process, while (TD)DFT analysis revealed the presence of quartets as well. With three key advancements of realizing the first iron complex showing dual luminescence, a MLCT luminescence and a world record MLCT lifetime, the results constitute a basis for future application of iron complexes as white light emitters and new photocatalytic reactions making use of the Janus-type properties of the developed complex.

Benchmarking the Lifecycle of Knowledge Graphs - Röder, Michael; Sherif, Mohamed; Saleem, Muhammad; Conrads, Felix; Ngonga Ngomo, Axel-Cyrille (Knowledge Graphs for eXplainable Artificial Intelligence: Foundations, Applications and Challenges)
Keywords: dice group_aksw roeder sherif saleem fconrads ngonga

Applying edge-counting semantic similarities to Link Discovery: Scalability and Accuracy - Georgala, Kleanthi; Röder, Michael; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of Ontology Matching Workshop 2020)
With the growth in number and variety of RDF datasets comes an in- creasing need for both scalable and accurate solutions to support link discovery at instance level within and across these datasets. In contrast to ontology matching, most linking frameworks rely solely on string similarities to this end. The limited use of semantic similarities when linking instances is partly due to the current literature stating that they (1) do not improve the F-measure of instance linking approaches and (2) are impractical to use because they lack time efficiency. We revisit the combination of string and semantic similarities for linking instances. Contrary to the literature, our results suggest that this combination can improve the F-measure achieved by instance linking systems when the combination of the measures is performed by a machine learning approach. To achieve this in- sight, we had to address the scalability of semantic similarities. We hence present a framework for the rapid computation of semantic similarities based on edge counting. This runtime improvement allowed us to run an evaluation of 5 bench- mark datasets. Our results suggest that combining string and semantic similarities can improve the F-measure by up to 6% absolute.
Keywords: 2020 dice simba sherif hecate ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal roeder georgala

LIGON – Link Discovery with Noisy Oracles - Sherif, Mohamed; Dreßler}, Kevin; Ngonga Ngomo, Axel-Cyrille (Proceedings of Ontology Matching Workshop 2020)
Link discovery plays a key role in the integration and use of data across RDF knowledge graphs. Active learning approaches are a common family of solutions to address the problem of learning how to compute links from users. So far, only active learning from perfect oracles has been considered in the literature. However, real oracles are often far from perfect (e.g., in crowdsourcing). We hence study the problem of learning how to compute links across knowledge graphs from noisy oracles, i.e., oracles that are not guaranteed to return correct classification results. We present a novel approach for link discovery based on a probabilistic model, with which we estimate the joint odds of the oracles’ guesses. We combine this approach with an iterative learning approach based on refinements. The resulting method, Ligon, is evaluated on 10 benchmark datasets. Our results suggest that Ligon configured with 10 iterations and 10 training examples per iteration achieves more than 95% of the F-measure achieved by state-of-the-art algorithms trained with a perfect oracle. Moreover, Ligon outperforms batch learning approaches devised to be trained with small amounts of training data by more than 40% F-measure on average.
Keywords: 2020 dice simba sherif ligon ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal kevin

Tentris – A Tensor-Based Triple Store - Bigerl, Alexander; Conrads, Felix; Behning, Charlotte; Sherif, Mohamed; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (The Semantic Web -- ISWC 2020)
Keywords: sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:simba sys:relevantFor:limbo sys:relevantFor:raki daikiri speaker tentris knowgraphs bigerl fconrads saleem sherif ngonga group_aksw dice

ProBERT: Product Data Classification with Fine-tuning BERT Model - Zahera, Hamada Mohamed Abdelsamee; Sherif, Mohamed (Proceedings of Mining the Web of HTML-embedded Product Data Workshop (MWPD2020))
Keywords: 2020 dice zahera sherif knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal

LIGER – Link Discovery with Partial Recall - Georgala, Kleanthi; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of Ontology Matching Workshop 2020)
Modern data-driven frameworks often have to process large amounts of data periodically. Hence, they often operate under time or space constraints. This also holds for Linked Data-driven frameworks when processing RDF data, in particular, when they perform link discovery tasks. In this work, we present a novel approach for link discovery under constraints pertaining to the expected recall of a link discovery task. Given a link specification, the approach aims to find a subsumed link specification that achieves a lower run time than the input specification while abiding by a predefined constraint on the expected recall it has to achieve. Our approach, dubbed LIGER, combines downward refinement oper- ators with monotonicity assumptions to detect such specifications. We evaluate our approach on seven datasets. Our results suggest that the different implemen- tations of LIGER can detect subsumed specifications that abide by expected recall constraints efficiently, thus leading to significantly shorter overall run times than our baseline.
Keywords: 2020 dice simba sherif hecate ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limes limbo opal georgala

„Wir müssen die Sorgen der Menschen ernst nehmen“ – Zur sprachlichen Thematisierung von Sorge und Angst in der Politik - Georgi, Christopher (Diskurs – ethisch)

Prudence and prevention: Empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik
Theoretical papers show that optimal prevention decisions in the sense of selfprotection (i.e., primary prevention) depend not only on the level of (second-order) risk aversion but also on higher-order risk preferences such as prudence (third-order risk aversion). We study empirically whether these theoretical results hold and whether prudent individuals show less preventive (self-protection) effort than non-prudent individuals. We use a unique dataset that combines data on higher-order risk preferences and various measures of observed real-world prevention behavior. We find that prudent individuals indeed invest less in self-protection as measured by influenza vaccination. This result is driven by high risk individuals such as individuals >60 years of age or chronically ill. We do not find a clear empirical relationship between riskpreferences and prevention in the sense of self-insurance (i.e. secondary prevention). Neither risk aversion nor prudence is related to cancer screenings such as mammograms, Pap smears or X-rays of the lung.
Keywords: prudence; risk preferences; prevention; vaccination; screening

Sprachsensible Formulierung von Erhebungsinstrumenten - Schwabl, Franziska; Janssen, Elmar; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

»auch auf gesanglichem Gebiete überaus thätig«. Max Reger und das Lied - Ried, Dennis (Musik in Baden-Württemberg. Jahrbuch 2019/20)

Do product testing programs lead to more favorable online reviews? (ausgezeichnet mit Best Paper Award) - Garnefeld, I.; Krah, T.; Böhm, Eva; Gremler, D. D. (2020 AMA Winter Academic Conference, San Diego, CA)

Manufacturers’ service growth through mergers and acquisitions – An event study - Eggert, A.; Böhm, Eva; Akalan, R.; Gebauer, H. (2020 AMA Winter Academic Conference, San Diego, CA)

Literarisches Wissen vom marxistischen Wissenschaftsbetrieb. Historiographische Ideologiedebatten in Gerti Tetzners „Karen W.“ - Elit, Stefan (Wirkendes Wort)

Dei ex machina: The Interaction Order of Gamified Distance Learning - Erofeeva, M.A.; Klowait, Nils (Sociology of Power)
The article analyzes the implementation of an online educational module and its impact on the organization of the classroom’s interaction order. The latter is institutionally constrained by the presence of a goal and the distribution of roles between teacher and students. The introduction of a digital learning platform adds a technological context to the institutional setting. The article considers technologies as possessing communicative affordances — opportunities for action made possible or delimited through their use. Technologies bring new interactive resources to the process of education and can affect the organization of the classroom’s interaction order. Using multimodal conversation analysis, we analyzed video recordings of the telemediated interaction of Russia-based students and teachers within a gamified online educational module. We investigate a case in which a student’s correct answer is nevertheless corrected by the teacher. We demonstrate that the teacher initiates the correction because they are guided by the ordering of the game elements within the interface. Based on a detailed analysis of the teacher’s mouse movement in relation to ongoing turns-at-talk, we show that this orientation is sustained by all participants. The work contributes to classroom interaction studies and affordance theory and develops the methodology of multimodal transcription for mediated contexts. The primary result of the study is an empirical demonstration that the relevance of technological affordances for interactants is situationally produced, and that this process is associated with the interweaving of the institutional and technical context of interaction. The conclusion discusses the relationship between affordances and institutional norms.

The Head-Fake Effect in Basketball Is Based on the Processing of Head Orientation, but Not on Gaze Direction - Weigelt, Matthias; Güldenpenning, Iris; Steggemann-Weinrich, Yvonne (Psychology)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Electrify your Game! Anodal tDCS Increases the Resistance to Head Fakes in Basketball - Friehs, Maximilian A.; Güldenpenning, Iris; Frings, Christian; Weigelt, Matthias (Journal of Cognitive Enhancement)
Keywords: General Medicine

Drivers and outcomes of salespersons’ value opportunity recognition competence in solution selling - Böhm, Eva; Eggert, Andreas; Terho, Harri; Ulaga, Wolfgang; Haas, Alexander (Journal of Personal Selling and Sales Management)
Keywords: Management of Technology and Innovation; Human Factors and Ergonomics

Is the head-fake effect in basketball robust against practice? Analyses of trial-by-trial adaptations, frequency distributions, and mixture effects to evaluate effects of practice - Güldenpenning, Iris; Schütz, Christoph; Weigelt, Matthias; Kunde, Wilfried (Psychological Research)
Reactions to the pass of a basketball player performing a head fake are typically slower than reactions to a basketball player who passes without a head fake (i.e., head-fake effect). The present study shows that extensive practice reduces the head-fake effect in basketball. Additional analyses were conducted to explore the mechanism behind the reduced head-fake effect. First, we analyzed whether or not participants developed some control over the processing of irrelevant gaze direction, as indicated by specific trial-to-trial adaptations (i.e., congruency sequence effect). Second, we fitted the individual frequency distributions of RTs to ex-Gaussian distributions, to evaluate if practice specifically affects the Gaussian part of the distribution or the exponential part of the distribution. Third, we modeled individual RT distributions as the so-called mixture effects to examine whether the way irrelevant gaze direction impacts performance (either occasionally but massively or continuously but moderately) changes with practice. The analyses revealed that the effect of practice could not be explained with an increasing congruency-sequence effect. Also, it could not be found in the ex-Gaussian distributional analyses. The assumption that residual failure to inhibit the processing of the gaze direction in contrast to continuous failures to do so might favor mixed effects over uniform effects at later courses of practice could not be validated. The reduced head-fake effect thus is argued to source in participants’ general increasing ability to inhibit the processing of the task-irrelevant gaze direction information and/or in a priority shift of gaze processing to a processing of the pass direction.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Social cues can impact complex behavior unconsciously - Schütz, Christoph; Güldenpenning, Iris; Koester, Dirk; Schack, Thomas (Scientific Reports)
Abstract In three experiments, we investigated the effect of unconscious social priming on human behavior in a choice reaction time task. Photographs of a basketball player passing a ball to the left/right were used as target stimuli. Participants had to respond to the pass direction either by a whole-body (complex) response or a button-press (simple) response. Visually masked stimuli, showing both a task-relevant cue (pass direction) and a task-irrelevant, social cue (gaze direction), were used as primes. Subliminal social priming was found for kinematic (center of pressure) and chronometric measures (response times): gaze direction in the primes affected responses to the pass direction in the targets. The social priming effect diminished when gaze information was unhelpful or even detrimental to the task. Social priming of a complex behavior does not require awareness or intentionality, indicating automatic processing. Nevertheless, it can be controlled by top-down, strategic processes.
Keywords: Multidisciplinary

Head-fake perception in basketball: the relative contributions of expertise, visual or motor training, and test repetition - Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (International Journal of Sport and Exercise Psychology)
Keywords: Applied Psychology; Social Psychology

Processing deceptive information in sports: Individual differences for responding to head fakes depends on the attentional capability of the observer - Güldenpenning, Iris; Weigelt, Matthias; Memmert, Daniel; Klatt, Stefanie (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Cognitive load reduces interference by head fakes in basketball - Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (Acta Psychologica)
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Negotiating weights for burden sharing rules in international climate negotiations: an empirical analysis - Kesternich, Martin; Löschel, Andreas; Ziegler, Andreas (Environmental Economics and Policy Studies)
Abstract We have collected data from a world-wide survey among COP delegates to empirically investigate preferences for certain burden sharing rules among key groups in a setting that reflects the possibility of observing concessions from negotiating partners. In our survey, the participants had the opportunity to select and combine up to eight (pre-defined) burden sharing rules and to assign relative weights to the selected rules in their preferred bundle. We examine whether such a mechanism helps to overcome the currently strictly (self-interested) strategic claims on equity in the negotiation process. We observe that delegates from different groups of countries show a general willingness for concessions. However, the degree to which different burden sharing rules are taken into consideration partly differs between countries. As a key insight we report that the individual assessment of the polluter-pays rule based on current emissions does not only stress the persistence of the traditional Annex-B/Non-Annex-B division but also suggests tendencies for a more fragmented grouping with different positions between, for example, delegates from developing countries (i.e. G77 members) and emerging countries (i.e. BASIC). At the same time, we observe tendencies for a more harmonized view among key groups towards the ability-to-pay rule in a setting of weighted burden sharing rules.
Keywords: Management; Monitoring; Policy and Law; Economics and Econometrics

Electrify your game! Anodal tDCS increases the resistance to head fakes in basketball - Friehs, Maximilian A; Güldenpenning, Iris; Frings, Christian; Weigelt, Matthias (Journal of Cognitive Enhancement)

Valence-dependent changes of neural processing of augmented feedback after extensive practice of a new motor task - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Zwischen Trend und Tradition: die Vielfalt des klassischen Gerätturnens und der innovativen Formen des Sichbewegens im Sportunterricht ausgeglichen nutzen. - Köster, Carolin; Kehne, Miriam (Sportpädagogik)

Fitnessstudio Turnhalle : Schülerinnen und Schüler lernen verschiedene Methoden des (hoch-)intensiven Intervalltrainings an klassischen Turngeräten kennen - Köster, Carolin (Sportpädagogik)

Bericht zur 52. Tagung der Arbeitsgemeinschaft für Sportpsychologie: Neues Format, unbekannte Talente und Belohnungsaufschub - Güldenpenning, Iris (Zeitschrift für Sportpsychologie)
Keywords: Applied Psychology; Physical Therapy; Sports Therapy and Rehabilitation; Social Psychology

No effect of social cues in antisocial behavior: The head-fake effect in basketball is not based on the processing of eye gaze direction - Weigelt, Matthias; Güldenpenning, Iris; Steggemann-Weinrich, Y. (Zukunft der Sportpsychologie zwischen Verstehen und Evidenz. Abstractband der 52. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Worauf basiert der Blicktäuschungseffekt im Basketball? Stimulus-Stimulus (S-S) vs. Stimulus-Response (S-R) Interferenz - Polzien, A.; Güldenpenning, Iris; Weigelt, Matthias (Zukunft der Sportpsychologie zwischen Verstehen und Evidenz. Abstractband der 52. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

The head-fake effect in basketball is based on the automating processing of head orientation, but not on gaze information - Weigelt, Matthias; Güldenpenning, Iris; Ste, Y. (Abstracts of the 62nd Conference of Experimental Psychologists (TeaP))

Electrify your Game! Anodal tDCS Increases the Resistance to Head Fakes in Basketball in basketball - Friehs, M.; Güldenpenning, Iris; Frings, C.; Weigelt, Matthias (Abstracts of the 62nd Conference of Experimental Psychologists (TeaP))

Temporal distance between head turn and pass modulates the head fake effect in basketball - Polzien, A.; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 62nd Conference of Experimental Psychologists (TeaP))

Producing deceptive actions in sports: The costs of generating head fakes in basketball - Güldenpenning, Iris; Weigelt, Matthias; Kunde, W. (Abstracts of the 62nd Conference of Experimental Psychologists (TeaP))

Anpassungseffekte an spielerspezifische Häufigkeiten von Blicktäuschungen im Basketball - Güldenpenning, Iris; Böer, Nils Tobias; Kunde, Wilfried; Weigelt, Matthias (Zukunft der Sportpsychologie zwischen Verstehen und Evidenz. Abstractband der 52. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Lernen und Gedächtnis im Sport - Weigelt, Matthias; Krause, Daniel; Güldenpenning, Iris (Sportpsychologie: Grundlagen und Anwendung)

Experimental analysis and modelling of bond formation in ultrasonic heavy wire bonding - Schemmel, Reinhard; Scheidemann, Claus; Hemsel, Tobias; Kirsch, Olaf; Sextro, Walter (CIPS 2020; 11th International Conference on Integrated Power Electronics Systems)
Ultrasonic wire bonding is a process to form electrical connections in electronics well established industry. Typically, a clamping tool is pressed on the wire and forced to vibrate at relative high frequency 40 to 100 kHz. The ultrasonic vibration is transmitted through the wire into the interface between wire and substrate. Due to frictional processes, contamination like oxide layers are removed from the contact zone, the surface roughness is reduced, and with increasing bond duration an metallic connection of wire and substrate is established. It is known that the amount of ultrasonic energy over time directly influences the strength and reliability of the bond connection, but the determination of optimum bond parameters is still a challenging experimental task. For this, in the past different model approaches have been presented, to calculate the bond quality by simulation. Measuring the friction between wire and substrate to validate these models is a challenging task at ultrasonic bonding frequency. Therefore a versatile test rig for bonding experiments at frequencies lower than 1 kHz is setup to get detailed insight into the different phases of the connection process. It includes a piezoelectric force sensor for the measurement of the three-dimensional process forces, an electrodynamic shaker for the vibration excitation and a conventional tension-compression testing machine to apply the bond normal force. Using this test rig, it is possible to observe the different phases of bond formation in detail, validate and enhance existing models and finally optimize bond parameters for different processes.

Schwingungen - Magnus, Kurt; Popp, Karl; Sextro, Walter
Schwingungsprobleme in der Technik analysieren, verstehen und beschreiben Schwingungen treten als nützliche oder auch als störende Erscheinungen fast überall in Natur und Technik auf. Deshalb ist es wichtig, sie zu verstehen, zu deuten oder auch in gewünschter Weise zu beeinflussen. Dieses Lehrbuch gibt eine Einführung in die physikalischen Grundlagen und die mathematische Behandlung von Schwingungen. In der aktuellen Auflage wurden der Text und die Bilder überarbeitet sowie konstruktive Hinweise von Fachkollegen berücksichtigt. Der Inhalt Grundbegriffe und Darstellungsmittel - Freie Schwingungen - Selbsterregte Schwingungen - Parametererregte Schwingungen - Erzwungene Schwingungen - Koppelschwingungen - Kontinuumsschwingungen - Chaotische Bewegungen - Aufgaben und Ergebnisse Die Zielgruppe Studierende der Ingenieurwissenschaften, der Physik und der Mathematik, berufstätige Ingenieure

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (2020 21st International Conference on Thermal, Mechanical and Multi-Physics Simulation and Experiments in Microelectronics and Microsystems (EuroSimE))

Evaluation of time series forecasting approaches for the reliable crack length prediction of riveted aluminium plates given insufficient data - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (PHM Society European Conference)
In all fields, the significance of a reliable and accurate predictive model is almost unquantifiable. With deep domain knowledge, models derived from first principles typically outperforms other models in terms of reliability and accuracy. When it may become a cumbersome or an unachievable task to build or validate such models of complex (non-linear) systems, machine learning techniques are employed to build predictive models. However, the accuracy of such techniques is not only dependent on the hyper-parameters of the chosen algorithm, but also on the amount and quality of data. This paper investigates the application of classical time series forecasting approaches for the reliable prognostics of technical systems, where black box machine learning techniques might not successfully be employed given insufficient amount of data and where first principles models are infeasible due to lack of domain specific data. Forecasting by analogy, forecasting by analytical function fitting, an exponential smoothing forecasting method and the long short-term memory (LSTM) are evaluated and compared against the ground truth data. As a case study, the methods are applied to predict future crack lengths of riveted aluminium plates under cyclic loading. The performance of the predictive models is evaluated based on error metrics leading to a proposal of when to apply which forecasting approach.
Keywords: PHM 2019; crack propagation; forecasting; unevenly spaced time series; step ahead prediction; short time series

Evaluating FPGA Accelerator Performance with a Parameterized OpenCL Adaptation of Selected Benchmarks of the HPCChallenge Benchmark Suite - Meyer, Marius; Kenter, Tobias; Plessl, Christian (2020 IEEE/ACM International Workshop on Heterogeneous High-performance Reconfigurable Computing (H2RC))
FPGAs have found increasing adoption in data center applications since a new generation of high-level tools have become available which noticeably reduce development time for FPGA accelerators and still provide high-quality results. There is, however, no high-level benchmark suite available, which specifically enables a comparison of FPGA architectures, programming tools, and libraries for HPC applications. To fill this gap, we have developed an OpenCL-based open-source implementation of the HPCC benchmark suite for Xilinx and Intel FPGAs. This benchmark can serve to analyze the current capabilities of FPGA devices, cards, and development tool flows, track progress over time, and point out specific difficulties for FPGA acceleration in the HPC domain. Additionally, the benchmark documents proven performance optimization patterns. We will continue optimizing and porting the benchmark for new generations of FPGAs and design tools and encourage active participation to create a valuable tool for the community. To fill this gap, we have developed an OpenCL-based open-source implementation of the HPCC benchmark suite for Xilinx and Intel FPGAs. This benchmark can serve to analyze the current capabilities of FPGA devices, cards, and development tool flows, track progress over time, and point out specific difficulties for FPGA acceleration in the HPC domain. Additionally, the benchmark documents proven performance optimization patterns. We will continue optimizing and porting the benchmark for new generations of FPGAs and design tools and encourage active participation to create a valuable tool for the community.
Keywords: FPGA; OpenCL; High Level Synthesis; HPC benchmarking

Accurate Sampling with Noisy Forces from Approximate Computing - Rengaraj, Varadarajan; Lass, Michael; Plessl, Christian; Kühne, Thomas (Computation)
In scientific computing, the acceleration of atomistic computer simulations by means of custom hardware is finding ever-growing application. A major limitation, however, is that the high efficiency in terms of performance and low power consumption entails the massive usage of low precision computing units. Here, based on the approximate computing paradigm, we present an algorithmic method to compensate for numerical inaccuracies due to low accuracy arithmetic operations rigorously, yet still obtaining exact expectation values using a properly modified Langevin-type equation.